Heterarchy: The Organization of Dissonance - Stark, David (Journal of Economic Sociology, 2010)
The ﬁ rst chapter of “The Sense of Dissonance: Accounts of Worth in Economic Life” by David Stark is about the challenges of contemporary organization and internal organizational changes happenning as the answer to these challenges.One of the key problems facing modern organization – is the challenging search questions. The fundamental challenge is the kind of search during which you do not know what you are looking for but will recognize it when you ﬁ nd it. In terms of John Dewey, this constitute perplexing situation. However these situations also provide new possibilities. Instead of avoiding perplexing situations, organizations can embrace them. Instead of merely responding to external situations as they happen to present themselves, organizations can foster organizational forms that regularly and recursively produce perplexing situations within the organization itself. Stark asserts that often this is taking place in reality.Such organizational form that differs from a hierarchy of command and a conceptual hierarchy of cognitive categories represents a heterarchy.Multiple evaluative principles are typical to heterarchy. Where the organizational environment is turbulent and there is uncertainty about what might constitute a resource under changed conditions, contending frameworks of value can themselves be a valuable organizational resource. Entrepreneurship then, in this view, exploits uncertainty. Entrepreneurship is the ability to keep multiple evaluative principles in play and to exploit the resulting friction of their interplay.Two key features that are at work with regard to heterarchy are discussed in this chapter. In contrast to the vertical authority of hierarchies, heterarchies are characterized by more crosscutting network structures, reﬂ ecting the greater interdependencies of complex collaboration. The other feature of heterarchy is that there is no hierarchical ordering of the competing evaluative principles.The results of the empirical application of his approach Stark presents in the following chapters.